Further Insight into the Conversion of a Ni-Fe Metal-Organic Framework during Water-Oxidation Reaction - Salmanion, Mahya; Nandy, Subhajit; Chae, Keun Hwa; Najafpour, Mohammad Mahdi (American Chemical Society, 2022)
Metal-organic frameworks (MOFs) are extensively investigated ascatalysts in the oxygen-evolution reaction (OER). A Ni-Fe MOF with 2,5-dihydroxy terephthalate as a linker has been claimed to be among the mostefficient catalysts for the oxygen-evolution reaction (OER) under alkalineconditions. Herein, the MOF stability under the OER was reinvestigated byelectrochemical methods, X-ray diffraction, X-ray absorption spectroscopy, energy-dispersive spectroscopy, scanning electron microscopy (SEM), transmissionelectron microscopy, nuclear magnetic resonance, operando visible spectroscopy,electrospray ionization mass spectroscopy, and Raman spectroscopy. The peakscorresponding to the carboxylate group are observed at 1420 and 1520 cm-1usingRaman spectroscopy. The peaks disappear after the reaction, suggesting theremoval of the carboxylate group. A drop in carbon content but growth in oxygencontent after the OER was detected by energy-dispersive spectra. This shows thatafter the OER, the surface of MOF is oxidized. SEM images also show deep restructures in the surface morphology of this Ni-FeMOF after the OER. Nuclear magnetic resonance and electrospray ionization mass spectrometry show the decomposition of thelinker in alkaline conditions and even in the absence of potential. These experimental data indicate that during the OER, thesynthesized MOF transforms to a Fe-Ni-layered double hydroxide, and the formed metal oxide is a candidate for the OER catalysis.Generalization is not true; however, taken together, thesefindings suggest that the stability of Ni-Fe MOFs under harsh oxidationconditions should be reconsidered.